2020
DOI: 10.1038/s41598-020-67474-9
|View full text |Cite
|
Sign up to set email alerts
|

Measuring robustness of brain networks in autism spectrum disorder with Ricci curvature

Abstract: Ollivier–Ricci curvature is a method for measuring the robustness of connections in a network. In this work, we use curvature to measure changes in robustness of brain networks in children with autism spectrum disorder (ASD). In an open label clinical trials, participants with ASD were administered a single infusion of autologous umbilical cord blood and, as part of their clinical outcome measures, were imaged with diffusion MRI before and after the infusion. By using Ricci curvature to measure changes in robu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…In addition to our application of curvature to cluster various cancerous datasets, the concept of curvature also finds its way in numerous applications such as computer vision, signal processing, and machine learning [2, 4, 20]. Anish et al used curvature to measure changes in robustness of brain networks in children with autism spectrum disorder [16]. Elkin et al found correlation between Ricci curvature and distinct survival outcomes for a set of patients with ovarian cancer using protein-protein interactive (PPI) networks and gene copy number alterations (CNAs) [7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to our application of curvature to cluster various cancerous datasets, the concept of curvature also finds its way in numerous applications such as computer vision, signal processing, and machine learning [2, 4, 20]. Anish et al used curvature to measure changes in robustness of brain networks in children with autism spectrum disorder [16]. Elkin et al found correlation between Ricci curvature and distinct survival outcomes for a set of patients with ovarian cancer using protein-protein interactive (PPI) networks and gene copy number alterations (CNAs) [7].…”
Section: Introductionmentioning
confidence: 99%
“…Another related work 25 characterized the brain networks affected by Autism Spectrum Disorder ( asd ) using Ollivier–Ricci curvature. Individuals with asd have altered white matter developmental patterns compared to individuals without asd .…”
Section: Introductionmentioning
confidence: 99%
“…Autologous cord blood infusion, a potential therapy, is believed to reduce neuro-inflammation and promote white matter development, thus triggering a reconfiguration of connectivity patterns in the brain. Simhal et al 25 used the Ollivier–Ricci network curvature (based on the mass transportation distance) to quantify the changes in the brain network after administering asd patients a single infusion of autologous umbilical cord blood. They calculated the Spearman correlation between changes in clinical behavioral scores and changes in curvature following treatment, and identified a relationship between clinical improvement and altered curvature in three white matter pathways that are implicated in social and communication abilities.…”
Section: Introductionmentioning
confidence: 99%
“…They also show that ORC can be used to identify changes in brain structural connectivity related to ASD and healthy aging. Simhal et al (Simhal et al, 2020) used ORC to measure changes in brain structural connectivity of individuals with ASD before and after the infusion of autologous umbilical cord blood. ORC has also been used to study differences in brain structural connectivity networks of cognitively impaired and non-impaired multiple sclerosis patients (Farooq et al, 2020).…”
Section: Introductionmentioning
confidence: 99%